Newcastle Disease Virus Infection of L Cells - Hecht, Toby T. (1974)
Newcastle disease virus (NDV) California strain reportedly grows poorly in L cells but replicates very well in chicken embryo cells. NDV-infected L cell cultures show a characteristic virus growth curve with respect to uridine incorporation, but plaque assays of the virus produced 24 h postinfection (PI) show no infectious particles when assayed on L cell monolayers and only a very low titer on chick cell monolayers. Plasma membranes isolated and purified from infected L cells 8 h PI contain all of the major virion proteins. In addition, NDV-infected L cells show a 50% loss of H-2 antigenic activity, a phenomenon previously observed in cells productively infected with vesicular stomatitis virus. These results suggest that at least part of the normal process of NDV maturation occurs in NDV-infected L cells. Sodium dodecyl sulfate-polyacrylamide gel patterns of supernatant virus purified from cells radiolabeled with amino acids from 3 to 24 h PI in the presence of actinomycin D show that all the major NDV structural proteins are present. Electron micrographs of NDV-infected L cells show extensive virus maturation at cell membranes. It can be concluded that infection of L cells with NDV results in a normal production of virus-specific RNA, synthesis of all the major structural proteins, association of the viral envelope proteins with the L cell plasma membrane, and the loss of cell surface H-2 antigenic activity. However, most of the virus particles produced are noninfectious.